Immigration, Search, and Redistribution: A Quantitative Assessment of Native Welfare - Michele Battisti; Gabriel J. Felbermayr; Giovanni Peri; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the effects of immigration on native welfare in a general equilibrium model featuring two skill types, search frictions, wage bargaining, and a redistributive welfare state. Our quantitative analysis suggests that, in all 20 countries studied, immigration attenuates the effects of search frictions. These gains tend to outweigh the welfare costs of redistribution. Immigration has increased native welfare in almost all countries. Both high-skilled and low-skilled natives benefit in two thirds of countries, contrary to what models without search frictions predict. Average total gains from immigration are 1.25% and 1.00% for high and low skilled natives, respectively.
Keywords: F22; J61; J64; 330; immigration; search; labor market frictions; fiscal redistribution; cross-country comparisons